Potensi pengembangan hunian vertikal di Kawasan Stasiun Solo Jebres - Rinanda Vitiastuti; Raden Chrisna Trie Hadi Permana; Hakimatul Mukaromah (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2026)
Rapid urban growth in Surakarta, combined with high population density and limited residential land availability, has increased the need for alternative development strategies through vertical housing development. Transit-oriented areas represent strategic locations for vertical housing due to their accessibility and proximity to urban activity centers. This study aims to analyze the potential for vertical housing development in the Solo Jebres Station area, one of the main transportation nodes in Surakarta. A deductive quantitative approach was employed using spatial overlay analysis. The variables include land suitability, earthquake hazard conditions, accessibility, population density, proximity to government centers, and land-use diversity. The results indicate that the area has high potential for vertical housing development, supported by suitable land conditions, non-earthquake-prone areas, good accessibility, and various urban infrastructure. Supporting infrastructure includes transportation networks, pedestrian paths, open spaces, commercial areas, public facilities, and drainage, solid waste, and clean water networks. Areas with the highest potential for vertical housing development are located in Kepatihan Wetan, western Purwodiningratan, Tegalharjo, and northern Jebres sub-districts. These findings provide an important basis for sustainable transit-oriented regional development planning in Surakarta.